Pilot study: self-medication among pregnant woman at Klinik Kesihatan in Kuala Muda District, Kedah - Manson, Lea Christine; Ismail, Nur Ain Najihah; Zulkifli Samba, Nurul Fathiah (2017)
Self-medication is described as the selection and use of non-prescription medications including herbal and traditional products by individuals to treat self-recognized illnesses and symptoms. Self-medication is widely practised by the society of all backgrounds. However, this study will only focus on the use of self-medication among pregnant woman. Our study was conducted at Klinik Kesihatan in Kuala Muda District, Kedah, which is a clinic for mothers and children. We spent 2 months from September to October of 2016 to collect our data for the research. The participants voluntarily agreed to help use to complete our survey by answering a set of questionnaire provided. The aim of this study is to evaluate the reasons of self-medication and the type of medications commonly used by pregnant women at Klinik Kesihatan in Kuala Muda District, Kedah. From the 100 filled questionnaires, we tabulated the data by using Statistical Package for the Social Sciences (SPSS) 16 Software and Microsoft Word 2010. By studying the data collected, we found out the most common medicine taken by pregnant women at Klinik Kesihatan in Kuala Muda District, Kedah was vitamins, followed by analgesic or painkiller, herbal remedies, anti-histamine, antacid, cough syrup, antibiotics , and some of them take others than listed medication. There were several reasons why people practising self-medication during pregnancy. The highest reason chosen by respondents are because of weakness, headache and stomach-ache they experienced during their pregnancy. There is growing evidence that self-medication among pregnant women are common in most developing countries. It is a challenge that requires attention because of the potential threat not only to the women but also to her unborn child. Most women are not aware of the contraindication of drugs in pregnancy and which drug is dangerous to them and their unborn child.